Lagoon morphology as an overarching driver for perch breeding success - Westerbom, Mats; Kuningas, Sanna; Lappalainen, Antti; Veneranta, Lari (Frontiers in Marine Science, 2023)
Fish spawning and nursery habitats are critically important for the maintenance and conservation of viable fish stocks. Understanding habitat use of breeding fish is therefore important. This study examines the spatial distribution of Eurasian perch (Perca fluviatilis) egg strand occurrence and larval density in 18 brackish water post-glacial land-uplift lagoons in the northern Baltic Sea. The aim of the study was to quantify spawning habitat characteristics and evaluate how geomorphological, hydrological, and biological parameters affect perch breeding. Egg strand occurrence was assessed by snorkeling whereas fish larvae and zooplankton were sampled using horizontal surface hauls. Egg strand and larval density increased with higher habitat isolation, i.e., bay morphology had a decisive role in determining early recruitment success. Moreover, egg strand occurrence and larval density correlated positively with water temperature, charophyte cover and negatively with salinity. The zooplankton community structure differed among lagoon types but neither zooplankton density nor diversity showed a clear association with egg strand or fish larvae abundance. However, cladocerans and copepods were abundant in the most enclosed bays, and their density correlated positively with perch larval density. Our findings comply with earlier studies highlighting the importance of bay isolation for fish recruitment strength. We call for a foreseeing coastal management planning, that apart from considering current status and trends, also integrates decadal long projections of isostatic land-uplift processes in conservation decisions to secure the long-term persistence of the best spawning and nursery areas.